2012
DOI: 10.3138/cmlr.68.2.111
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Language Proficiency, Social Networking, and Language Use during Study Abroad: Learners’ Perspectives

Abstract: This study examines the self-perceived speaking proficiency development of 204 learners of Japanese who studied abroad in Japan and analyzes connections between self-reported social network development, language use, and speaking development. Learners perceived that they gained the most in areas associated with the intermediate and advanced levels of the ACTFL (American Council on the Teaching of Foreign Languages) Speaking Proficiency Guidelines and the least in novice and superior-level abilities, largely be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
78
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 46 publications
4
78
1
Order By: Relevance
“…How can a student of French return from a semester in France ostensibly knowing less French than she did before her departure (Kinginger 2008)? The search for answers to these questions has normally entailed efforts to quantify various aspects of students' experiences, such as their use of time (Freed, Segalowitz, and Dewey 2004) or the size, intensity, or durability of their local social networks (Dewey, Bown, and Eggett 2012). While these studies indicate links between student activity and learning, they do not necessarily explain this relationship.…”
Section: Introductionmentioning
confidence: 99%
“…How can a student of French return from a semester in France ostensibly knowing less French than she did before her departure (Kinginger 2008)? The search for answers to these questions has normally entailed efforts to quantify various aspects of students' experiences, such as their use of time (Freed, Segalowitz, and Dewey 2004) or the size, intensity, or durability of their local social networks (Dewey, Bown, and Eggett 2012). While these studies indicate links between student activity and learning, they do not necessarily explain this relationship.…”
Section: Introductionmentioning
confidence: 99%
“…However, language barriers have also been identified as a major source of stress for international students, affecting both the academic and sociocultural domains of their experiences. They can also affect self-esteem (Benson, Barkhuizen, Bodycott, & Brown, 2012) and can be perceived as a barrier to the development of social networks, particularly friendship with locals (Dewey, Bown, & Eggett, 2012). Academically, language difficulties affect the students' abilities to understand teachers and fellow students, to take part in seminars, and to complete course readings and assignments (Andrade, 2006;Savicki, Arrúe, & Binder, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In such studies (Freed ; Trenchs‐Parera ) the SA learners are normally found to obtain greater gains than their AH peers, reportedly because of the differential amount of input the SA and AH groups receive. Although there is variation in the extent to which SA learners engage in L2 activities and social networks (Kinginger ; Dewey et al ), the SA context theoretically offers many more opportunities for meaningful language use and greater exposure to authentic L2 input than the typical AH context, which is limited to the 3–4 hours of class a week. Given such large differences in what SA and AH contexts typically offer in terms of language exposure and practice, it is hardly surprising that many studies report an advantage for the SA over the AH learning context.…”
Section: Literature Reviewmentioning
confidence: 99%